Metal and Microbiological Analysis of Drinking Water Quality in Bideha and Sahidnagar Municipalities of Dhanusha District of Nepal - Jha, Randhir Kumar; Sha , Priyanka Kumar; Mishra, Pawan Kumar; Bhattarai, Ajaya; Yadav, Chandradip Kumar; Bahfie, Fathan (THE ACADEMIA, 2026)
The primary objectives of this study were to compare the drinking water quality in the Dhanusha District, specifically in the Bideha and Sahidnagar Municipalities, using the Nepal Drinking Water Quality Standards (NDWQS, 2022), and to identify any potential health risks associated with physicochemical and microbiological contamination. 14 groundwater samples were taken from hand pumps in the two Municipalities as part of the cross-sectional study design. Using standard titration and experimental techniques, each sample was examined for physicochemical parameters, including Iron, calcium, and magnesium. Escherichia coli (E. coli) and total coliforms were measured using the membrane filtering technique to evaluate the microbiological quality. The major findings showed that most physicochemical parameters were within NDWQS limits: iron (0.11–0.22 mg/L), calcium (33.67–56.11 mg/L), and magnesium (1.94–15.06 mg/L). However, total coliforms (60–195 CFU/100 mL) and E. coli (2–10 CFU/100 mL) were detected in several samples, indicating faecal contamination and potential health risks. These results emphasize the need for routine microbiological monitoring, improved sanitation practices, and community education to ensure safe drinking water in Bideha and Sahidnagar Municipalities.